Regulation of Parents' Emotions of Child Victims of Sexual Violence - Eka Indah Nurmawati; Dwiyana Indah Safitri (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Cases of sexual violence in Indonesia have increased every year. The cases of sexual violence occurred from various ages, ranging from teenagers, children, and toddlers. According to data from the KPAI itself, throughout 2022 there were 4,683 complaints of sexual violence. Apart from having an impact on victims, cases of sexual violence also have an impact on parents. Support and assistance from parents play a very important role for victims. Therefore, parental skills in regulating emotions related to cases of sexual violence are very important. According to Gross and John (in Paula & Miftakhul, 2021) emotion regulation is the ability of individuals to regulate their thoughts and behaviour consciously or unconsciously during different emotions, including positive and negative emotions. This study aims to look further at the dynamics of parental emotional regulation in accompanying and directing children who are victims of sexual violence. The method used in this research is qualitative with an instrumental case study approach with 2 parents of child victims of sexual violence as research subjects. Collecting data using interviews and observation. This research resulted in the finding that both parents of children who were victims of sexual violence were able to regulate emotions better, in which there was a helping role in the family. This research can be used as a reference for dealing with the problem of emotional regulation of parents of child victims of sexual violence, and in the future, they are better prepared to accompany or direct them, so they don't experience trauma in the future.Kasus kekerasan seksual di Indonesia mengalami peningkatan di setiap tahunnya. Adapun kasus kekerasan seksual terjadi dari berbagai usia, mulai dari remaja, anak dan juga balita. Menurut data dari KPAI sendiri, di sepanjang tahun 2022 ada aduan sebanyak 4.683 kasus kekerasan seksual. Selain memberikan dampak terhadap korban, kasus kekerasan seksual juga berdampak terhadap orang tua. Support dan pendampingan dari orang tua sangat berperan bagi korban. Oleh karena itu ketrampilan orang tua dalam meregulasi emosi terkait kasus kekerasan seksual ini sangat penting. Menurut Gross dan John (dalam Paula & Miftakhul, 2021) regulasi emosi merupakan kemampuan individu untuk secara sadar atau tidak sadar mengatur pikiran dan perilaku mereka selama emosi yang berbeda, termasuk emosi positif dan negatif. Penelitian ini bertujuan untuk melihat lebih jauh bagaimana dinamika regulasi emosi orang tua dalam mendampingi dan mengarahkan anak yang menjadi korban kekerasan seksual. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pedekatan studi kasus instrumental dengan 2 orang tua dari anak korban kekerasan seksual sebagai subjek penelitian. Pengumpulan data menggunakan wawancara dan observasi. Penelitian ini menghasilkan temuan bahwa kedua orang tua dari anak korban kekerasan seksual mampu meregulasi emosi menjadi lebih baik, dimana didalamnya terdapat peran keluarga yang membantu. Adapun penelitian ini dapat dijadikan salah satu acuan untuk menangani permasalahan regulasi emosi orang tua dari anak korban kekerasan seksual, serta kedepannya lebih siap dalam mendampingi atau mengarahkannya sehingga tidak mengalami trauma dikemudian hari.